2017
DOI: 10.1038/eye.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of age-related macular degeneration in an elderly UK Caucasian population—The Bridlington Eye Assessment Project: a cross-sectional study

Abstract: ImportanceThere is paucity of data on prevalence and disease asymmetry of age-related macular degeneration (AMD), particularly the earlier stages, in the UK population.Objective and PurposeTo determine the prevalence of age-related macular degeneration in an elderly Caucasian UK population.DesignCross-sectional population study, 2002-2006.ParticipantsResidents in the study area of Bridlington aged 65 years and older.MethodsFull-ophthalmic examination was undertaken in 3549 participants, of eligible 6319 Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 40 publications
2
37
0
2
Order By: Relevance
“…Previous reports on the prevalence and associations of PPCNV are based on case reports or small case series from hospital data. To the best of our knowledge, there are no reports on population prevalence of PPCNV except for our previous report of worse eye prevalence of 0.29% for Grade 4c (PPCNV), compared to 1.8% for neovascular AMD (nAMD) (grade 4b AMD) and 2.5% for geographic atrophy (GA) (grade 4a AMD) [12]. Furthermore, there are no data available in the literature on the population prevalence of asymptomatic PPCNV.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous reports on the prevalence and associations of PPCNV are based on case reports or small case series from hospital data. To the best of our knowledge, there are no reports on population prevalence of PPCNV except for our previous report of worse eye prevalence of 0.29% for Grade 4c (PPCNV), compared to 1.8% for neovascular AMD (nAMD) (grade 4b AMD) and 2.5% for geographic atrophy (GA) (grade 4a AMD) [12]. Furthermore, there are no data available in the literature on the population prevalence of asymptomatic PPCNV.…”
Section: Introductionmentioning
confidence: 90%
“…The BEAP study methods, including image acquisition and analysis, have been reported previously [12]. In summary, the BEAP is a single centre population-based prevalence study, with the primary objective to investigate the utility of screening for eye disease in an elderly population ≥65 years, using clinical examination by trained optometrists and digital imaging technology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No genetic testing was performed on the population, and no electrooculograms were undertaken. Eyes with drusen were not excluded (given their high prevalence within this age group) [8], unless they were the dominant clinical feature with suspicion of a central drusenoid pigment epithelial detachment. No family history data were recorded for the majority of patients.…”
Section: Methodsmentioning
confidence: 99%